2010
DOI: 10.1007/s10734-010-9404-9
|View full text |Cite
|
Sign up to set email alerts
|

E-technology and work/life balance for academics with young children

Abstract: Since the late 1980s, research on post-industrialized economies shows that the boundary between work and family is increasingly becoming blurred. The continuing evolution of e-technology allows work for some to be done anywhere, anytime. This article examines the degree to which e-technology has transferred work into the home lives of academics and how this has affected their work/life balance. Drawing on a study in an Australian university of academics with young children, we utilise the terms 'work extensifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
145
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(162 citation statements)
references
References 21 publications
8
145
1
8
Order By: Relevance
“…Such observations support the work of other researchers who noted that while technology provides flexibility and allows employees to work anywhere (Brough & Kalliath, 2009), it has also blurred the lines between work and home (Sarker, Xiao, Sarker, & Ahuja, 2012). In fact, technological advancements may benefit organizations more than employees (Currie & Eveline, 2011). Gen X participants in the current study would agree.…”
Section: Technology Is a Help And Hindrance To Work-life Integrationmentioning
confidence: 63%
“…Such observations support the work of other researchers who noted that while technology provides flexibility and allows employees to work anywhere (Brough & Kalliath, 2009), it has also blurred the lines between work and home (Sarker, Xiao, Sarker, & Ahuja, 2012). In fact, technological advancements may benefit organizations more than employees (Currie & Eveline, 2011). Gen X participants in the current study would agree.…”
Section: Technology Is a Help And Hindrance To Work-life Integrationmentioning
confidence: 63%
“…Husbands' greater involvement in housework could be attributed to wives having less time for these activities (Bianchi, Robinson, & Milkie, 2006). Coltrane (2000) points out that although the majority of men and women agree that household chores and childcare should be shared, very few men assume equal responsibility for household labour, and most wives still carry the greatest responsibility (Craig 2007;Currie & Eveline, 2011). In contrast, Zimmerman (2003 found in her study of 47 dual-career couples in the United States that both spouses shared housework equally.…”
Section: Household Chores and Childcarementioning
confidence: 99%
“…In general, most professions, including academia have become more demanding. This trend has consequently compelled academics to work beyond normal office hours (Currie & Eveline, 2010;Santos & Cabral-Cardoso, 2008). Jacobs and Winslow (2004) found that full-time assistants, associate professors or full-time professors in various faculties exceeded working 50 hours per week.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, most of this work is performed after hours such as during evenings, weekends and on holidays (Kinman & Jones, 2008;O'Laughlin & Bischoff, 2005). Currie and Eveline (2010) reported that almost half of the academics in their sample accessed their work emails daily during their annual leave while a third accessed their work emails once a week. In addition, academics on study leave also accessed their work emails on a daily basis (Currie & Eveline, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation